From the history of control and seed business in Ukraine: the meaning and role of N.N. Kuleshov in its formation (1908–1926) - I. V. Balian (History of science and technology, 2016)
It covers the activities of the scientist-grower N.N. Kuleshov (1890–1968) in the context of the development of domestic control of seeds. It is not only deeply versed in the theoretical and practical problems of seed production and selection, but also the main principles of the organization and functioning of the control system. He made a significant contribution to its formation: Central led the seed of the Ukrainian SSR station, worked on the Kharkov Plant Breeding Station, participated in the All-Ukrainian Society of seed, congresses and meetings, developed a core program based on scientific and research activities of seed control stations. Along with other important problems crop area selection, seed were one of the major in its activities, especially in the first half of the work.